Epigenetic modifications and their roles in pediatric brain tumor formation: emerging insights from chromatin dysregulation - Kawata, Kento; Chapman, Owen S.; Narumi, Satoshi; Kawauchi, Daisuke (Frontiers in Oncology, 2025)
Pediatric brain tumors, the most devastating cancers affecting children, are believed to originate from neural stem/progenitor cells in developing brain. In precise timing and specific regions during the brain development, chromatin deregulation plays crucial roles in redirecting normal neuronal differentiation pathways toward tumorigenesis. Indeed, epigenomic abnormalities are thought to be more important for brain tumor formation especially in children than adults, as pediatric brain tumors generally exhibit fewer genetic mutations compared to adult brain tumors. Given the small number of mutations, targeting such limited alterations involved in cancer epigenomes is expected to be more effective in pediatric brain tumors. The mechanisms of cancer epigenomes include mutation or dysregulation of chromatin remodelers, histone modifiers, histones themselves, and DNA methylation enzymes. Furthermore, genomic rearrangements and/or higher-order chromatin topology also contribute to these epigenomic mechanisms. These mechanisms are commonly observed in various types of pediatric brain tumors. However, alterations in chromatin regulatory factors differ across tumor types, reflecting the unique epigenetic landscapes shaped by their tumor origins. Accordingly, clarifying their functional similarities and differences across tumor types could offer valuable insights for finding new therapeutic strategies. Thus, this review article focuses on elucidating how pediatric brain tumors arise from epigenomic deregulation and what epigenetic molecules or mechanisms could serve as therapeutic targets.